2020
DOI: 10.3390/ijerph17031012
|View full text |Cite
|
Sign up to set email alerts
|

Encounters with Persons Who Frequently Use Psychiatric Emergency Services: Healthcare Professionals’ Views

Abstract: Encounters and interactions between healthcare professionals and patients are central in healthcare services and delivery. Encountering persons who frequently use psychiatric emergency services (PES), a complex patient group in a complex context, may be particularly challenging for healthcare professionals. The aim of the study was to explore healthcare professionals’ experiences of such encounters. Data were collected via individual interviews (N = 19) and a focus group interview with healthcare professionals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…A recent qualitative study conducted in Sweden explored the experience of encounters with frequent users of psychiatric ED among nurses and physicians. 17 The main findings revealed that psychiatric ED nurses and physicians found their encounters with frequent users as "caring, professional, and human processes" requiring specific abilities, such as self-awareness, self-acceptance, and self-compassion. Another qualitative study conducted with the same sample explored ED staff understanding of frequent users and their needs.…”
mentioning
confidence: 99%
“…A recent qualitative study conducted in Sweden explored the experience of encounters with frequent users of psychiatric ED among nurses and physicians. 17 The main findings revealed that psychiatric ED nurses and physicians found their encounters with frequent users as "caring, professional, and human processes" requiring specific abilities, such as self-awareness, self-acceptance, and self-compassion. Another qualitative study conducted with the same sample explored ED staff understanding of frequent users and their needs.…”
mentioning
confidence: 99%
“…When initial contextual barriers were overcome the RG intervention had the potential to provide staff with new perspectives on mental health and recovery, organizational capacity to integrate a recovery approach and users with a meaningful outlet of lived experience to influence treatment goals. The actual delivery provided staff with experiences and tools to ‘do things with users’, to start a conversation, listen, learn, share and plan for care and recovery goals and, to reach common grounds, which previous research has emphasized 2,12,15 …”
Section: Discussionmentioning
confidence: 99%
“…The actual delivery provided staff with experiences and tools to ‘do things with users’, to start a conversation, listen, learn, share and plan for care and recovery goals and, to reach common grounds, which previous research has emphasized. 2 , 12 , 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include psychiatric crisis and emergency departments, the creation of mobile psychiatric teams, crisis hotlines, and psychiatric reception centers. The use of psychiatric emergency departments has particularly increased over the last decades ( Schimdt et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%